2015
DOI: 10.1146/annurev-matsci-070214-020823
|View full text |Cite
|
Sign up to set email alerts
|

What Is High-Throughput Virtual Screening? A Perspective from Organic Materials Discovery

Abstract: A philosophy for defining what constitutes a virtual high-throughput screen is discussed, and the choices which influence decisions at each stage of the 'computational funnel' are investigated, including an indepth discussion of the generation of molecular libraries. Additionally advice on the storing, analysis and visualization of data is given, based upon extensive experience in the group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
214
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 263 publications
(232 citation statements)
references
References 78 publications
0
214
0
3
Order By: Relevance
“…Here, a virtual screening technique, which is an effective method in time-critical problems ( 25 ), was applied to determine the structure and energy of an interface. This virtual screening technique has been used in drug discovery, in which a prediction model is constructed using machine learning from a relatively small data set and a large database consisting of the actual data, and the data predicted by the prediction model are constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a virtual screening technique, which is an effective method in time-critical problems ( 25 ), was applied to determine the structure and energy of an interface. This virtual screening technique has been used in drug discovery, in which a prediction model is constructed using machine learning from a relatively small data set and a large database consisting of the actual data, and the data predicted by the prediction model are constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Because the structure and properties of molecules are determined by the laws of quantum mechanics, ultimately chemical discovery must be based on fundamental quantum principles. Indeed, electronic structure calculations and intelligent data analysis (machine learning) have recently been combined aiming towards the goal of accelerated discovery of chemicals with desired properties12345678. However, so far the majority of these pioneering efforts have focused on the construction of reduced models trained on large data sets of density-functional theory calculations.…”
mentioning
confidence: 99%
“…The experimental results showed that the two selected cases had higher average heat collection rates than all the existing cases in our previous measurement database. Being similar to a previous chemical HTS concept proposed by Pyzer-Knapp et al [52], we reconstruct the process of this …”
Section: High-throughput Screening (Hts)mentioning
confidence: 96%